HBR's 10 must reads on strategic marketing. - Harvard (Harvard Business Review Press Harvard Business Review Press, 2013)
If you read nothing else on marketing that delivers competitive advantage, read these 10 articles. We?ve combed through hundreds of articles in the Harvard Business Review archive and selected the most important ones to help you reinvent your marketing by putting it―and your customers―at the center of your business.
Includes index.
Keywords: Marketing--Management.